In vitro seed germination and seedling development of Phaius tancarvilleae (L’Her.) Blume. - Pant, Bijaya; Shrestha, Sumitra; Pradhan, Shreeti (Scientific World, 2011)
In vitro seed germination and seedling development of Phaius tancarvilleae (L’Her.) Blume. was carried out on 0.8%(w/v) agar solidified MS Medium (Murashige and Skoog, 1962) without hormones or supplemented with different concentration and combination of Naphthalene acetic acid (NAA) and 6-benzylaminopurine (BAP). MS medium supplemented with 0.5 mg/l of BAP was the most ideal condition for early seed germination, protocorm formation and development of seedlings. Germination started after 7 weeks of culture and complete seedlings were obtained after 24 weeks of culture. This protocol might be helpful for mass propagation of orchids by asymbiotic seed germination. Keywords: Orchid; Invitro; Protocorm; Media DOI: http://dx.doi.org/10.3126/sw.v9i9.5518 SW 2011; 9(9): 50-52